Postponed moult of primary coverts untangles the ageing of Wrynecks Jynx torquilla. Issue 2 (3rd July 2017) - Laesser, Jacques; van Wijk, Rien E.
ABSTRACT: In most bird species, all feathers are moulted at least once per year, usually after breeding (complete post-breeding moult). Woodpeckers (Picidae) often retain some primary coverts and secondaries during their otherwise complete post-breeding moult. To date, this phenomenon has received little attention and has not been studied thoroughly in European woodpeckers, even though it could prove very helpful for ageing and therefore for demographic studies. We studied the moult patterns of breeding adult Wrynecks Jynx torquilla in a Swiss Alpine valley between 2013 and 2016. Due to intensive ringing in the study area prior to the current study, our data set included birds of known age. Some individuals were captured and their moult documented in up to four years in a row. We found that Wrynecks present an extreme case of delayed primary-covert moult. No primary covert (PC) was renewed during the post-juvenile moult. At most three PCs were renewed by the second post-breeding moult and three to six at more advanced ages. That some juvenile PCs were retained until the sixth calendar year has not previously been documented for a species with such a relatively short lifespan. This principle of 'postponed moult' in Wrynecks affects the appearance of the PCs differently in each age class and allows us to age birds more accurately than previous methods. Here we describe how to interpret the moult pattern of PCs to age Wrynecks properly and argue that the moult strategy of Wrynecks was hitherto incompletely and in many cases mistakenly understood, leading to confusion in the ageing of Wrynecks.